Poorly Differentiated Neuroendocrine Tumor of the Rectum Coexistent with Giant Rectal Villous Adenoma Presenting as McKittrick-Wheelock Syndrome - Sammy G. Nakhla; Traci T. Murakami; Srinath Sundararajan (Case Reports in Oncological Medicine)
McKittrick-Wheelock Syndrome is a rare disorder, noted for electrolyte and fluid depletion caused by secretory colorectal adenomas and carcinomas. We report here the first reported case of a 55-year-old man with a large rectal villous adenoma coexistent with a poorly differentiated neuroendocrine tumor of rectum presenting with McKittrick-Wheelock Syndrome. Palliative chemotherapy resulted in complete resolution of symptoms and improved quality of life.